2022
DOI: 10.1088/1755-1315/1033/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on heart rate performance of eel (Anguila bicolor)

Abstract: Temperature changes affect fish behavior, and it is one of the critical factors which influence fish survival. The optimum temperature of a species can be used to detect the presence of fish. The fish heart rate indicates the effect of temperature on fish physiology. This study aims to determine the effect of temperature on the fish heart rate and its recovery time. The study collected the heart rate data by observing 40 eels (Anguila bicolor ) measuring 36±0.30 cm and body weight <200 g at 21, 25, and 31°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The contraction frequency of the SCCs correlated highly with temperature [29]. A steady and significant increase in their frequency with increasing temperature and vice versa was observed [29], as found in the in vivo condition in fish and mammals [37][38][39].…”
Section: Cell Physiologysupporting
confidence: 53%
See 1 more Smart Citation
“…The contraction frequency of the SCCs correlated highly with temperature [29]. A steady and significant increase in their frequency with increasing temperature and vice versa was observed [29], as found in the in vivo condition in fish and mammals [37][38][39].…”
Section: Cell Physiologysupporting
confidence: 53%
“…This includes exploring the effects of temperature fluctuations and changes in oxygen levels on cardiac cells, allowing researchers to manipulate temperature and oxygen concentrations to simulate hypoxic or hyperoxic conditions to overall mimic different climate scenarios in vitro. In this way, the effects of temperature and oxygen changes on cardiomyocyte viability, contractility, electrical activity, and overall cardiac function can be assessed, allowing further investigation of the biological mechanisms underlying cardiomyocyte behavior under adverse environmental conditions [37][38][39][40][41][42][43][44]. Moreover, extensive research has demonstrated the influence of temperature on cardiac contractility across vertebrates [24,37,41,42].…”
Section: Climate Modelmentioning
confidence: 99%